Pengembangan Bahan Ajar Kurikulum Merdeka pada Pembelajaran Tematik Berbasis Kontekstual Kearifan Lokal untuk Kelas 5 Sekolah Dasar - Aqilla, Y.A. Rini Shafa; Putra, M. Jaya Adi; Zufriady, Zufriady (ARZUSIN, 2024)
Teaching materials are prepared systematically and designed in accordance with applicable curriculum provisions. Currently, the education curriculum in Indonesia has changed to the Independent Curriculum. In the Independent Curriculum, a thematic approach is used in Education Units so that they can choose subject or thematic approaches freely based on students learning needs or based on local wisdom. The aim of this research was to develop valid independent curriculum teaching materials for contextually based of thematic learning of local wisdom for grade 5 elementary schools. This research was Research and Development (R&D) development research with a 4D development model, consist of Define, Design, Develop and Disseminate. The data collection techniques used were interviews, assessment sheets and questionnaires. The subjects in this research was 10 class V students of SD Negeri 006 Sekip Hulu Rengat. The data analysis technique used to analyze quantitative data on validator assessment sheet instrument used the Aiken index. The research results obtained from the media expert validation test were 0.94 (very valid), the material expert validation test was 0.87 (very valid), the student response questionnaire was 89% (very practical) and the teacher response questionnaire was 90% (very practical). The final results on the student test obtained an overall average of 95% and were categorized as very good so that the teaching material product was suitable for use.